2016
DOI: 10.1111/jsbm.12228
|View full text |Cite
|
Sign up to set email alerts
|

Seizing Opportunities: The Moderating Role of Managerial Characteristics on the Relationship between Opportunity-Seeking and Innovation Efficacy in Small Businesses

Abstract: We draw from regulatory focus theory to examine the relationship between a focus on opportunities through strategic orientation and entrepreneurial culture and managerial reports of innovation efficacy in small businesses. We propose that manager goals and behaviors moderate these relationships. Hypotheses were tested on a sample of 352 small employer firms. Findings support that strategic orientation positively associates with innovation efficacy and that this relationship is stronger under low managerial dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 110 publications
0
20
1
1
Order By: Relevance
“…Dalborg and Wincent (2015) determine that there is a positive relationship between business entrepreneurship and ESE. Among the business characteristics, some research demonstrates that strategic orientation and organizational culture are positively related to ESE, since this variable provides opportunities for indirect learning (Cooper et al, 2016). Within the institutional environment and culture, researchers have resorted to social cognitive theory to analyze whether culture and institutional environment impact ESE (Newman et al, 2018).…”
Section: Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Dalborg and Wincent (2015) determine that there is a positive relationship between business entrepreneurship and ESE. Among the business characteristics, some research demonstrates that strategic orientation and organizational culture are positively related to ESE, since this variable provides opportunities for indirect learning (Cooper et al, 2016). Within the institutional environment and culture, researchers have resorted to social cognitive theory to analyze whether culture and institutional environment impact ESE (Newman et al, 2018).…”
Section: Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Hence, we argue for a mediating relationship between CSE and proactive personality on innovative behavior. This investigation should provide new understanding how factors affecting innovative behavior must be central in the discussion of entrepreneurial competitiveness (see Cooper, Peake & Watson, 2016).…”
Section: Psychological Research On Urban Societymentioning
confidence: 99%
“…Chen and Zhou (2017) found that entrepreneurial self-efficiency positively relates to innovation thanks to entrepreneurs' motivation to be efficient at a personal and organizational level and to achieve goals. But there are studies (Shepherd, Patzelt, & Baron, 2013;Cooper, Peake, & Watson, 2016) that confirmed the relationship between self-regulation, personal characteristics, and the entrepreneur task and roles. However, this relationship was never proved in the Latin-American context.…”
Section: Social Entrepreneurshipmentioning
confidence: 99%